Softbit speech decoding a new approach to error concealment. - Fingscheidt, T. (IEEE Transactions on speech and audio processing)
In digital speech communication over noisy channels there is the need for reducing the subjective effects of residual bit errors which have not been eliminated by channel decoding. This task is usually called error concealment. We describe a new and generalizing approach to error concealment as part of a modified robust speech decoder. It can be applied to any speech codec standard and preserves bit exactness in the case of an error free channel. The proposed method requires bit reliability information provided by the demodulator or by the equalizer or specifically by the channel decoder and can exploit additionally a priori knowledge about codec parameters. We apply our algorithms to PCM, ADPCM, and GSM full-rate speech coding using AWGN, fading, and GSM channel models, respectively. It turns out that the speech quality is significantly enhanced, showing the desired inherent muting mechanism or graceful degradation behavior in the case of extreme adverse transmission conditions